Mitochondria-Targeted Nanocarriers Promote Highly Efficient Cancer Therapy: A Review - Zeng, Zeng; Fang, Chao; Zhang, Ying; Chen, Cong-Xian; Zhang, Yi-Feng; Zhang, Kun (Frontiers in Bioengineering and Biotechnology, 2021)
Mitochondria are the primary organelle that produce adenosine triphosphate (ATP), and they play vital roles in maintaining normal functions. They also regulated apoptotic pathways of cancer cells. Given that, designing therapeutic agents that precisely target mitochondria is of great importance for cancer treatment. Nanocarriers can combine the mitochondria with other therapeutic modalities in cancer treatment, thus showing great potential to cancer therapy in the past few years. Herein, we summarized lipophilic cations- and peptides- based nanosystems for mitochondria targeting. This review described how mitochondria-targeted nanocarriers promoted highly efficient cancer treatment in photodynamic therapy (PDT), chemotherapy, combined immunotherapy and sonodynamic therapy (SDT). We further discussed mitochondria-targeted nanocarriers’ major challenges and future prospects in clinical cancer treatment.